Islamic religious education in Kabardino-Balkaria in the soviet and post-soviet periods: transfor-mation, dynamics, current state - Aleksandra N. Takova (Кавказология, 2024)
The study examines the changes that took place in the system of Islamic religious education in Kabardino-Balkaria during the Soviet and post-Soviet periods. The article describes the structure and features of the network of Muslim schools and colleges that functioned in the subregion before 1917. The article analyzes the policy of the Soviet authorities in relation to Muslim educational institutions and its regional specifics. It is concluded that in Kabardino-Balkaria, an extensive network of Tibetan schools was active until the end of the 20s of the XX century. Its almost complete elimination is associated with the mass peasant unrest that took place in the late 20s and early 30s of the XX century. Attention is focused on the religious component that was vividly present in the ideology of the rebellious peasants and the active role of the local clergy in them. The characteristic of the period of the 30-80s of the XX century is given – the time when religious education was virtually absent from the structure of the religious culture of the republic. The features of the development and complexity of the process of reviving the system of religious education that took place in the post-Soviet period are considered. The current state of this system is assessed, and its current problems are identified.